The Military History of Tsarist Russia
VI, 266 p.
Keywords: The Military History of Tsarist Russia examines Russian military history from the rise of the Muscovite state to the present, even peeking briefly into the future. The volume covers Russia's land forces extensively, but also covers the development of the Russian Navy, and the creation and development of the Russian Air Force - parts of the Russian military machine that are frequently neglected in general writings. The historical analysis addresses the development and function of the Russian military whether in peace or in war, as well as the impact of war and changes in the military upon Russian society and politics. Questions of military organization, doctrine, and technique are paramount, as well as the critical question of the interface between the armed forces and society.